Developing ‘Happiness Engineering’ Subject for the Schools in India: Designing the Pedagogical Framework for a Sustainable Happiness Curriculum - Ashraf Alam; Atasi Mohanty (Qubahan Academic Journal)
The aim of this research was to develop the ‘Happiness Engineering’ subject by designing a ‘sustainable happiness curriculum’ and ‘pedagogical framework’ for the schools of India by adopting the whole school approach. Happiness Engineering subject is modelled like any other traditional school subject, e.g., History, Chemistry, or Computer Science. The researchers have prepared it by adopting the scientifically proven ‘global best practices’ exercised in different schools, colleges, and university departments across the globe in ‘sustainability education’, ‘adjectival education’, and ‘well-being education’. It has been adapted and contextualised to be implemented in Indian schools by considering the available infrastructural resources in existing Indian schools and bearing in mind the feasibility of its effective transaction. Experiences of 129 experts from India that included senior secondary school teachers, school counsellors, pedagogical scientists, learning theorists, health experts, people from NGOs, and professors of education, were used to modify and contextualize the prepared curriculum framework for the ‘Happiness Engineering’ subject to effectively cater the needs of Indian senior secondary school students.